Study of Ectonucleotidases and Adenosine Deaminases in Drosophila - Preuer, Kristina (Jihočeská univerzita, 2013)
Extracellular adenosine triphosphate and extracellular adenosine are important regulatory molecules in the human immune system. The concentrations of these molecules are in turn regulated by ectonucleotidases and adenosine deaminases. In this thesis I attempt to test the gene silencing efficiency of RNA interference for three different genes coding for such enzymes in the model organism Drosophila melanogaster.
Study of Ectonucleotidases and Adenosine Deaminases in Drosophila
Keywords: ectonucleotidases; adenosine deaminase; extracellular adenosine triphosphate; extracellular adenosine; NT5E-1; NT5E-2; ADGF-A; Drosophila melanogaster; ectonucleotidases; adenosine deaminase; extracellular adenosine triphosphate; extracellular adenosine; NT5E-1; NT5E-2; ADGF-A; Drosophila melanogaster